Kejujuran dan aktualisasi diri pada pekerja (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2023)
Individuals who experience self-actualization can be seen from a personal and social perspective. The responsibility of an individual symbolizes the character of honesty in facing reality, even when in a state of doubt and fear. This research aims to find out